Herbal medicine IMOD suppresses LPS-induced production of proinflammatory cytokines in human dendritic cells - Mirzaee, Saeedeh; Drewniak, Agata; Sarrami-Forooshani, Ramin; Kaptein, Tanja M.; Gharibdoost, Farhad; Geijtenbeek, Teunis B. H. (Frontiers in Pharmacology, 2015)
Traditional medicines that stimulate or modulate the immune system can be used as innovative approaches to treat immunological diseases. The herbal medicine IMOD has been shown to strongly modulate immune responses in several animal studies as well as in clinical trials. However, little is known about the mechanisms of IMOD to modulate immunity. Here we have investigated whether IMOD modulates the immunological function of human dendritic cells (DCs). IMOD alone did not induce DC maturation nor production of cytokines. Notably, IMOD decreased the production of pro-inflammatory cytokines IL-6, IL-12 p70 and TNFα by LPS-activated DCs at both mRNA and protein levels in a dose dependent manner. In contrast, treatment with IMOD did not affect LPS induced-production of the anti-inflammatory cytokine IL-10. Furthermore, IMOD inhibited T cell activation/proliferation by LPS-treated DCs and skewed T-cells responses towards the T helper type 2 polarization. These data strongly indicate that IMOD has a potent immunomodulatory ability that affects TLR signaling and thereby modulates DC function. Insight into the immunomodulatory effect of herbal medicine IMOD may provide innovative strategies to affect the immune system and to help combat various diseases